Organophosphorus Chemistry 2018 - Keglevich, György (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Organophosphorus chemistry is an important discipline within organic chemistry. Phosphorus compounds, such as phosphines, trialkyl phosphites, phosphine oxides (chalcogenides), phosphonates, phosphinates and >P(O)H species, etc., may be important starting materials or intermediates in syntheses. Let us mention the Wittig reaction and the related transformations, the Arbuzov- and the Pudovik reactions, the Kabachnik-Fields condensation, the Hirao reaction, the Mitsunobu reaction, etc. Other reactions, e.g., homogeneous catalytic transformations or C-C coupling reactions involve P-ligands in transition metal (Pt, Pd, etc.) complex catalysts. The synthesis of chiral organophosphorus compounds means a continuous challenge. Methods have been elaborated for the resolution of tertiary phosphine oxides and for stereoselective organophosphorus transformations. P-heterocyclic compounds, including aromatic and bridged derivatives, P-functionalized macrocycles, dendrimers and low coordinated P-fragments, are also of interest. An important segment of organophosphorus chemistry is the pool of biologically-active compounds that are searched and used as drugs, or as plant-protecting agents. The natural analogue of P-compounds may also be mentioned. Many new phosphine oxides, phosphinates, phosphonates and phosphoric esters have been described, which may find application on a broad scale. Phase transfer catalysis, ionic liquids and detergents also have connections to phosphorus chemistry. Green chemical aspects of organophosphorus chemistry (e.g., microwave-assisted syntheses, solvent-free accomplishments, optimizations, and atom-efficient syntheses) represent a dynamically developing field. Last, but not least, theoretical approaches and computational chemistry are also a strong sub-discipline within organophosphorus chemistry.